Non-selective feeding and oviposition behaviour of Cryptocephalus trifasciata (Coleoptera: Cerambycidae: Cryptocephalinae) precludes its use as a biological control agent for downy rose myrtle (Rhodomyrtustomentosa)*. Issue 3 (4th March 2017) - Smith, Melissa C.; Wheeler, Gregory S.; Barr, Kane L.; Brown, Bradley T.; Makinson, Jeffrey R.
ABSTRACT: Downy rose myrtle ( Rhodomyrtus tomentosa ), a southeast Asian native shrub, invades natural areas in Florida and Hawaii, where it forms dense, impenetrable thickets. We tested the host affinity and survivorship of a case-bearing beetle, Cryptocephalus trifasciata on R. tomentosa and related species. C. trifasciata adults and larvae fed, oviposited and/or completed development on all non-target species tested ( N = 11). C. trifasciata has a broad host range and is unsuitable for use as a biological control agent.